Sekularisasi dan Sekularisme Agama - Raden Datoek A. Pachoer (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2016)
The Starting from the 19Th centuries, the word of secularization appears, the secularization is intended to hand over power and property rights to the state church and secular foundations. And in the 20th century, the term has developed a conceptual long, so it has meaning and significance vary. While in Indonesia the word secularization or secularism is the word 'proscribed' was to talked. In Indonesia the issue of secularization first raised in the 1970s by Nurcholish Majid and reap the pros and contra. Differences of secularization and secularism, secularization is understood as the process of release of Life is no longer dominated by the religious institution or authority of religious institutions. Secularization is also be interpreted as a separation movement or extrication themselves from the power of religious institutions in its various aspects. While secularism is as an ideology or ideologies that deny the existence of a sacred setting. The leaders  agreed to the secularization and secularism modernization of Auguste Comte, for example, he announced that as a result of modernization, the people is grow beyond the "theological stage" in the evolution of social and religious at that time will be abandoned. It also resulted in the secularization of Modernization. Because the transformation is the shift in value is due to the attitude of the religious by growing who tend to adapt themselves to the structure of modern society, which is materialistic, rational and pragmatic and very demanding realization of subsistence. Positive side of secularism is as an ethical system, which teaches people to continue to improve their living standards that benefit by finding good in the world through human abilities without being bound and the reference to religion or religious doctrine that is supernatural. The downside of secularism is defined as the ideologies that reject sacred settings, resulting distrust of religion.